Studi Implementasi Program Nasional Pemberdayaan Masyarakat (PNPM) Mandiri Perkotaan di Kelurahan Bandarharjo Kecamatan Semarang Utara - Mumpuni, Diyah Tri; Maesaroh, Maesaroh (Journal of Public Policy and Management Review, 2014)
In order to achieve poverty reduction in Indonesia, the government launched programs through PNPM Urban empowerment. PNPM is sustainable poverty alleviation programs. The purpose of this study was to determine the influence of communication relationships (X1) with the successful implementation of the (Y); effect of executing (X2) with the successful implementation of the (Y), and the influence of communication (X1) and executive ability (X2) with the successful implementation of the (Y) PNPM Urban Village in Bandarharjo. Â This type of research is explanatory research using the techniques of data collection through questionnaires, interviews, and observations. The research sample of 34 respondents, drawn by simple random sampling method. Analysis of the data using quantitative methods of hypothesis testing using SPSS techniques Kendall Rank Correlation Coefficient, Coefficient Konkordasi Rank Kendall and coefficient of determination (KD). Â Based on the research results obtained show that the influence of communication (X1) with the implementation of PNPM (Y) based on the price of the Z count value is greater than the Z table at the significant level of 5% ie 2 â‰¥ 1.96 and the large influence of KD 5.76%. influence is shown by the ability of implementers (X2) with the implementation of PNPM (Y) with Z count value is greater than the Z table at 5% significance level is 1.96 and â‰¥ 2.16 large effect of KD 6.76%. The latest results show the influence of communication (x10 and executive ability (X2) with the implementation of PNPM (Y) is greater than 2hitung ï£ ï£ 2tabel or â‰¥ 50.72 86.721 KD was 43.2%. Â Â The research found that many people do not understand what Bandarharjo PNPM goal with certainty, the absence of information boards, employees who are not biased computer. In solving these problems BKM have much socialization to the community, as well as providing a means of communication such as bulletin boards or information and conduct computer training at BKM members.